2016
DOI: 10.5539/elt.v9n2p1
|View full text |Cite
|
Sign up to set email alerts
|

Lurking and L2 Learners on a Facebook Group: The Voices of the Invisibles

Abstract: This qualitative research investigates the practice of lurking among English as a second language (ESL) learners in a Facebook group discussion. Lurking is a term used to describe the activity of following and observing any online discussions or activities without contributing to the discussions. Lurkers are often accused of being invisible and passive participants. Facebook groups with international members usually uses English as the medium of communication in their group discussions. It is a norm for L2 lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
(12 reference statements)
1
8
0
Order By: Relevance
“…The actual number of students who commented on the Facebook Page was low, with the majority of students seemingly content to engage by reading the posts of others and the module manager. The explanation for this behavior is likely to be due to a broad variety of reasons, including the query already being asked by a fellow student, not wanting to come across as lacking knowledge, or conversely, being seen as a “know it all.” Previous studies have already highlighted the phenomenon of “lurking” on social media (Shafie et al, ) and it would not be surprising if a similar approach was present here. Moreover, seeing as social media is also an online space that many students face with trepidation due to the potential anonymity and privacy issues (Aydin, ), the development of a Facebook Page as an educational scaffold needs to be student‐centered and managed in such a way that promotes and supports interaction.…”
Section: Discussionsupporting
confidence: 57%
“…The actual number of students who commented on the Facebook Page was low, with the majority of students seemingly content to engage by reading the posts of others and the module manager. The explanation for this behavior is likely to be due to a broad variety of reasons, including the query already being asked by a fellow student, not wanting to come across as lacking knowledge, or conversely, being seen as a “know it all.” Previous studies have already highlighted the phenomenon of “lurking” on social media (Shafie et al, ) and it would not be surprising if a similar approach was present here. Moreover, seeing as social media is also an online space that many students face with trepidation due to the potential anonymity and privacy issues (Aydin, ), the development of a Facebook Page as an educational scaffold needs to be student‐centered and managed in such a way that promotes and supports interaction.…”
Section: Discussionsupporting
confidence: 57%
“…A lot of time, there are one-tomany broadcastings but little user-to-user interactions. There are five reasons for English as a second language (ESL) students in Malaysia to lurk in Facebook groups that use English as the medium of communication, which are; poor online communication skills, lack confidence, no sense of belonging, learning by lurking, and following the norm of Facebook groups (Shafie, Yaacob, & Singh, 2016). Many interviewees in this study similarly expressed that they were not confident with their L2 ability, and that the group members were not supportive of their efforts to promote learning.…”
Section: The Statistics Of the Group Activitiesmentioning
confidence: 99%
“…As students are ready for technological changes in learning (Manca & Ranieri, 2013), it is time that higher education (HE) institutions harness their potential to better serve the students' creative needs (Davis III, Deil-Amen, Rios-Aguilar, & González Canché, 2015). At present, Facebook, Twitter, and Instagram are popular forms of SNS with a high rate of university students' demography (Shafie, Yaacob, & Singh, 2016); hence could be employed as mobile learning tools to positively impact language learning.…”
Section: Students' Perceptions and Attitudes Towards The Use Of Instagram In English Language Writing Introductionmentioning
confidence: 99%
“…They provide new ways for languages and cultures which rope students in for critical reflection in the process of meaning making (Chun, Smith, & Kern, 2016). Facebook and Twitter offer wide opportunities for English language learners to interact with native speakers and authentic materials (Shafie et al, 2016). Shih (2011; reported that the Facebook writing activities among Taiwanese EFL students have improved their language and generic skills as well as strengthened peer-to-peer relationships.…”
Section: Students' Perceptions and Attitudes Towards The Use Of Instagram In English Language Writing Introductionmentioning
confidence: 99%